The effect of high-intensity interval training on the development of some special physical abilities and the achievement of the 100-meter sprint for young men - صدام, أ.م.د. انتصار مزهر; Lafta, Assist. Prof .Abbas Ali (Sulaimani Journal for Humanities, 2026)
The research included an introduction, importance, problem, objectives, and hypotheses. The research addressed the role of training methods and their types, especially high-intensity interval training, in short-distance running training, particularly the 100m sprintfor youth. The research included research procedures for selecting the sample according to the training requirements for this age group. The research addressed training within high-intensity interval training for physical abilities, such as transitional speed, maximum speed, and speed-related strength, within the requirements of the stages and achievement of the 100m sprint for youth. The training was in accordance with the requirements of high-intensity interval training, which is one of the methods that has a positive impact in reducing fatigue within compensation and recovery methods in non-oxygen work within the requirements of such a training system. The research sample was selected from youth clubs in Baghdad. The research concluded the role of such a training method in developing specific physical abilities, such as transitional speed, maximum speed, and speed-related strength, and their role in such a training method. It also recommended the use of such a method for other samples. The achievement of the sample members. The recommendations included the necessity of using other physical abilities in developing activities within.
Keywords: High; intensity interval training; physical abilities